1971
DOI: 10.1007/bf02638524
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition ofThalictrum L. seed oils

Abstract: The fatty acid composition of five representatives of the Thalictrum L. genus of the plant family Ranunculaceae has been investigated. The fatty acids include mainly acids with double bonds in the trans-5 position (about 60%). Although the main component of the fatty acids is a triene acid (trans-5,cis-9, cis-12-octadecatrienoic acid), the oils investigated are semidrying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
2
3
3
Order By: Relevance
“…The major components were octadeca-trans-5, cis-9, cis-12 trienoic and octadec-trans-5-enoic acids, each being about 30%. This trienoic acid (5t, 9c, 12c) was found in this study to be less in amount than reported in earlier studies for other Thalictrum species (1)(2)(3). Rankoff (3) found this acid to constitute ewer 40%.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The major components were octadeca-trans-5, cis-9, cis-12 trienoic and octadec-trans-5-enoic acids, each being about 30%. This trienoic acid (5t, 9c, 12c) was found in this study to be less in amount than reported in earlier studies for other Thalictrum species (1)(2)(3). Rankoff (3) found this acid to constitute ewer 40%.…”
Section: Resultscontrasting
confidence: 61%
“…When the solvent was removed on a rotary evaporator, a light green oil was obtained. Five grams of oil (10 parts by weight) was saponified (4) by refluxing with potassium hydroxide (3 parts by weight) in methanol (50 parts by volume) for 3 hours in an atmosphere of nitrogen gas. After saponification, the methanol was removed by distillation.…”
Section: Experimental1mentioning
confidence: 99%
“…The four other species did not contain any fatty acids with a A5 or A6 double bond.Fatty acids with chain lenght of 2 0 -2 4 carbon atoms were determ inated in sig nificant am ount only in C. pubescens 9.5 % of total fatty acid of 20:1. Our results were in good agreem ent with those of literature (Aitzetmiiller andTsevegsiiren, 1993 and1994;Bagby et al, 1962;Ferlay et al, 1993;Kaufmann and Barve, 1965;Rankoff et al, 1971;Smith et al, 1968;Spen cer et al, 1970;Takagi et al, 1983;Tsvegsiiren and Aitzetmiiller, 1993;Ustun et al, 1990;Viano and Gaydou, 1984;Vioque et al, 1994;Wu et al, 1980).…”
Section: Resultssupporting
confidence: 81%
“…Fatty acid composition of twenty eight species seed oils have been already reported (Bagby et al, 1962;Ferlay et al, 1993;Kaufmann and Barve, 1965;Rankoff et al, 1971;Smith et al, 1968;Spen cer et al, 1970;Takagi et al, 1983;Tsevegsüren and Aitzetmtiller, 1993;Ustun et al, 1990;Viano and Gaydou, 1984;Vioque et al, 1994;Wu et al, 1980). Among these, six species belonging to the genus A nem one displayed fair amounts of gammalinolenic acid (G L A ) or cis-6,cis-9,cis-12 18:3, in their lipids (Smith et al, 1968, Tsevegsüren andAitzetm üller, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the Ranunculaceae and in a number of other plant families, seed oils have been found that contain smaller or larger percentages of AS-18:3 acids (Smith, 1970;Takagi and Itabashi, 1982;Takagi et al, 1983). The most prominent of these is columbinic acid ( 5 t ,9c, 12~-18:3;Cb) in Aquilegiu (Kaufmann and Barve,196.5) and Thalictrum (Rankoff et al, 1971;Wu et al, 1980), two genera of the Ranunculaceae. In these species, all the A5 acids found apparently have the trans configuration.…”
Section: Introductionmentioning
confidence: 99%